Intermediate English - McQuade, Suzanne; Riggio, Laura; Living Language (Firm) (New York: Living Language, 2012)
Intermediate course, including coursebook, audio CDs, and online learning.
Intermediate English: Disc 4. The daily routine -- Work and school -- Disc 5. Work and school (cont.) -- Shopping and running errands -- Disc 6. On the phone -- Taking a trip.
Compact discs.
Discs are numbered continuously within a 3-part set (Essential, Intermediate, Advanced).
Keywords: English language -- Textbooks for foreign speakers; English language -- Sound recordings for foreign speakers; English language -- Self-instruction.; Anglais (Langue) -- Manuels pour allophones; Anglais (Langue) -- Enregistrements sonores pour allophones; English language; Audiobooks; Self-instruction; Sound recordings -- for foreign speakers; Textbooks -- for foreign speakers; Audiobooks; Livres audio